Political Uncertainty and Cost Stickiness: Evidence from National Elections around the World - Lee, Woo‐Jong; Pittman, Jeffrey; Saffar, Walid (Contemporary Accounting Research, 2020)
ABSTRACT By analyzing a large panel of elections in 55 countries, we show that political uncertainty surrounding elections can affect asymmetric cost responses to activity changes (i.e., cost stickiness). In comparison to non‐election years, we find that the asymmetry in cost behaviors is stronger during election years in regressions that control for other firm‐level and country‐level determinants. In another series of tests, we report strong, robust evidence supporting the predictions that the importance of political uncertainty to cost stickiness is concentrated in countries with sound political and legal institutions. Collectively, the results imply that managers retain slack resources when political uncertainty is high but to be resolved soon.